Aktivitas Biologis Asap Cair Batang Manggis (Garcinia mangostana L.) Terhadap Viabilitas Streptococcussp. (L.10.3) - Rikhsan Kurniatuhadi, Lilis Susanti Elvi Rusmiyanto (Universitas Tanjungpura, 2018)
The wood vinegar of the stem of mangosteen (G. mangostana L.) is the result of pyrolysis of the stem which is condensed into steam. Wood vinegar contains acid and phenol compounds that have antibacterial activities. This research aims to determine the biological activities of the wood vinegar of the stem of mangosteen (G. mangostana L.) on the viability of Streptococcus sp. (L.10.3) and determine the concentration of wood vinegar of the stem of mangosteen (G. mangostana L.) which is effective in inhibiting the growth of Streptococcus sp. (L.10.3). This research used a completely randomized design (CRD) with 6 treatments consisting of wood vinegar with a concentration of 0.1 (Tl); 0.5 (T2); 1 (T3) and 1.5% (T4), negative controls namely sterile distilled water (T5), and positive control namely chlorhexidine of 0.2% (T6). The viability test used the dilution method and calculation of the number of colonies using the total plate count (TPC) method, each treatment was repeated four times. The results showed the increasing concentration of wood vinegar of the stem of mangosteen (G. mangostana L.) and the decreasing amount of Streptococcus sp. (L.IO.3). Wood vinegar at concentration 1.5% showed bacterial growth of 6.9 x 105 CFU / ml which was very different from sterile distilled water by 2.5 x 107 CFU / ml with inhibition up to 96.9% and not significantly different from chlorhexidine of 0.2%.